Synthesis and electrochemical behavior of single-crystal magnetite nanoparticles - Santos, F. J. [UNESP]; Varanda, L. C.; Ferracin, L. C.; Jafelicci, M. [UNESP] (Amer Chemical Soc, 2008)
Water-dispersed magnetite nanoparticle synthesis from iron(II) chloride in dimethyl sulfoxide (DMSO)-water solution at different DMSO-water ratios in alkaline medium was reported. TEM and XRD results suggest a single-crystal formation with mean particle size in the range 4-27 nm. Magnetic nanoparticles are formed by the oxidative hydrolysis reaction from green rust species that leads to FeOOH formation, followed by autocatalysis of the adsorbed available Fe(II) on the FeOOH surfaces. The available hydroxyl groups seem to be dependent on the DMSO-water ratio due to strong molecular interactions presented by the solvent mixture. Goethite phase on the magnetite surface was observed by XRD data only for sample synthesized in the absence of DMSO. In addition, cyclic voltammetry with carbon paste electroactive electrode (CV-CPEE) results reveal two reduction peaks near 0 and +400 mV associated with the presence of iron(III) in different chemical environments related to the surface composition of magnetite nanoparticles. The peak near +400 mV is related to a passivate thin layer surface such as goethite on the magnetite nanoparticle, assigned to the intensive hydrolysis reaction due to strong interactions between DMSO-water molecules in the initial solvent mixture that result in a hydroxyl group excess in the medium. Pure magnetite phase was only observed in the samples prepared at 30% (30W) and 80% (80W) water in DMSO in agreement with the structured molecular solvent cluster formation. The goethite phase present on the, magnetite nanoparticle surface like a thin passivate layer only was detectable using CV-CPEE, which is a very efficient, cheap, and powerful tool for surface characterization, and it is able to determine the passivate oxyhydroxide or oxide thin layer presence on the nanoparticle surface.